The Sarawak State Appreciation Night 2017 - Amalia, Madihie (2017)
The Honourable Tan Sri Datuk Amar Hj Mohamad Morshidi bin Abdul Ghani has presented an Highest Performance Team Award to the SCS-ESP: Self-Value Excellence Module Programme on the 6th January 2017 at Grand Margaritha, Kuching, Sarawak at the Appreciation Night 2017. Three academia from Department of Counselling, Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS): Dr Amalia Madihie (Senior Lecturer), Salmah Mohamad Yusoff (Lecturer) and Siti Norazilah Mohd Said (Lecturer) involved directly in the 6 Shared Values interventions development. The project was initiated by the Chief's Minister Department by Riziandy Nawawi. Other team members are Hajjah Roseini Mohtar (from Chief's Minister Department) and Remy Sharmila Mohamed Sebli (from the Teacher Education Institute of Malaysia).